Evaluation of hearing protection device effectiveness for musicians. (1st March 2023) - Crawford, Kathryn; Willenbring, Krista; Nothwehr, Faryle; Fleckenstein, Stephanie; Anthony, T. Renee
Abstract: Objective: To evaluate musicians' personal attenuation and perceptions of three types of hearing protection devices (HPDs): formable foam earplugs and both non-custom and custom versions of uniform attenuation earplugs (UAEs) marketed to musicians. Design: A mixed-methods approach was used to evaluate the HPDs. Audiometric testing obtained hearing levels at baseline and with each HPD across frequencies (125–8000 Hz) to determine personal attenuation ratings and uniformity of attenuation. Participants completed surveys over six months regarding how often they used the HPDs and their perceptions about wearing them. Study sample: Twenty-four musicians were recruited to participate. Results: Substantial variability was observed in the attenuation achieved among participants for each HPD type, but custom UAEs provided the most consistent attenuation across frequencies. Participants' HPD preferences were influenced by multiple factors including personal instrument and specific activity. Custom UAEs were most frequently used but usage rates continually decreased over the 6-month period. Conclusions: Fit-testing is important to determine fit and sizing. Combining information on the effectiveness of HPDs with musicians' opinions about wearing them can inform recommendations for which types may be the most effective and feasible options for reducing sound exposures.